DEKOMPOSISI SERASAH DAUN Avicennia marinaPADA BERBAGAI TINGKAT SALINITAS Decomposition Avicennia marina Leaf Litter At Various Levels Of Salinity - Elisa Januarita Doloksaribu; Yunasfi Djayus; Zulham Apandy Harahap (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
The mangrove litter which has been decomposed contributes organic matter as food source for many species of fish and other organisms in the mangrove ecosystem. This study aims to determine the effect of salinity on the rate of leaf litter decomposition A. marina and to know the nutrient content of carbon (C), nitrogen (N) and phosphorus (P) in the A. marina litter leaf which been released during the decomposition time. This research was done at Hamparan Perak base Deli Serdang sub-district of North Sumatera Province during February until May 2017. The results of the study of leaf litter A. marina at 0-10 ppt salinity level more quickly decomposes. The average weight of the rest of the leaf litter A. marina which decompose at a rate of 0-10 ppt salinity, 10-20 ppt and 20-30 ppt yaitu 1,46 grams, 5,86 grams, dan 6,53 grams.The rate of leaf litter decomposition A. marina at a rate of 0-1 0 ppt salinity, 10-20 ppt and 20-30 ppt was 28.61, 17.68, and 14.97. Carbon levels of nutrients in the leaf litter A. marina ppt salinity level 0-10, 10-20 ppt and 20-30 ppt was 18,61%, 18,97%, and 18,58%. Levels of nutrients nitrogen in leaf litter A. marina ppt salinity level 0-10 ppt, 10-20 ppt and 20-30 ppt was 1,51%, 1,68%, and 1,18% . As well as the levels of the nutrient phosphorus leaf litter A. marina on ppt salinity level 0-10 ppt, 10-20 ppt and 20-30 ppt was 0,58%, 0,52%, and 0,51% respectively.Keywords :A. marina,decomposition, mangrove leaf litter, nutrients, salinity.